2022
DOI: 10.2147/idr.s374503
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mcr-1 Harboring Hypervirulent Klebsiella pneumoniae in Clinical Specimens and Lytic Activity of Bacteriophage KpnM Against Isolates

Abstract: Background The World Health Organization (WHO) has declared the multi-drug resistant (MDR) Klebsiella pneumoniae as one of the critical bacterial pathogens. The dearth of new antibiotics and inadequate therapeutic options necessitate finding alternative options. Bacteriophages are known as enemies of bacteria and are well-recognized to fight MDR pathogens. Methods A total of 150 samples were collected from different clinical specimens through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We really appreciate the authors and all collaborators who have recently reported their research results in an article entitled “Distribution of Mcr-1 Harboring Hypervirulent Klebsiella Pneumoniae in Clinical Specimens and Lytic Activity of Bacteriophage KpnM Against Isolates”. 1 This study had shown very encouraging research results and important information regarding the use of bacteriophage; KpnM phage in this case, which could be further studied for combating the antibiotic resistance issues. However, first of all, this study lacks clear determination of “hypervirulent” bacteria.…”
Section: Dear Editormentioning
confidence: 75%
“…We really appreciate the authors and all collaborators who have recently reported their research results in an article entitled “Distribution of Mcr-1 Harboring Hypervirulent Klebsiella Pneumoniae in Clinical Specimens and Lytic Activity of Bacteriophage KpnM Against Isolates”. 1 This study had shown very encouraging research results and important information regarding the use of bacteriophage; KpnM phage in this case, which could be further studied for combating the antibiotic resistance issues. However, first of all, this study lacks clear determination of “hypervirulent” bacteria.…”
Section: Dear Editormentioning
confidence: 75%
“…
We acknowledge the effort made by the author to craft the response to our recent publication in infection and drug resistance. 1 We are pleased that the author appreciated our work and found the results of the study promising to fight antibiotic resistance and resistant superbugs like Klebsiella pneumoniae. In addition to that, the author raised some fair queries regarding the methods and suggested possible explications.
…”
mentioning
confidence: 88%
“…Cases of HvKp are being reported more frequently globally, in wider Asia [ 71 , 79 , 80 , 81 ], Western Europe [ 82 , 83 , 84 , 85 , 86 ], Scandinavia [ 87 , 88 ], North America [ 63 , 88 , 89 , 90 ], South America [ 91 ], and Southern Africa [ 51 , 88 ]. This shows an ability for HvKp to spread into new environments and populations.…”
Section: Hypervirulent Klebsiella Pneumoniaementioning
confidence: 99%
“…The confluence of multi-drug resistance and hypervirulence has led to the development of extended-spectrum β-lactamase-producing HvKp (ESBL-HvKp) [ 49 , 109 ] and hypervirulent carbapenem-resistant Klebsiella pneumoniae (Hv-CRKp) strains [ 49 , 72 , 103 ]. These MDR-HvKp strains have been detected in Southeast Asia [ 68 , 72 ] and are spreading worldwide [ 49 , 79 , 103 , 109 , 110 , 111 ].…”
Section: Hypervirulent Klebsiella Pneumoniaementioning
confidence: 99%